ANALYSIS OF THE ECONOMIC EFFICIENCY AND INFLUENCING FACTORS OF SHAN TUYET TEA PRODUCTION AMONG FARMING HOUSEHOLDS IN YEN BINH COMMUNE, THAI NGUYEN PROVINCE (Isagoge - Journal of Humanities and Social Sciences, 2025)
Shan Tuyet tea is an important crop in Yen Binh Commune, Thai Nguyen Province (formerly Yen Cu Commune, Cho Moi District, Bac Kan Province). It plays a key role in helping local people increase their income. However, tea production still faces several challenges, such as low yield, small farming scale, limited use of machinery, and unstable markets. This study surveyed 45 farming households in two villages, dividing them into three groups by production scale (small, medium, and large). The research applied descriptive and comparative statistics, annual cost-benefit accounting, and multiple regression analysis. Results show that tea production has improved thanks to government support and the development of cooperatives. Still, there are clear differences between household groups. Larger-scale households achieved better yields and higher economic results because they had more land, invested more labor, and worked closely with cooperatives. The regression model found three factors that clearly increased tea yield: joining a cooperative, having more land, and using more labor. In contrast, education level and farming experience did not show significant effects. Based on the findings, the study proposes four main solutions to improve tea production: invest in equipment suitable for each group; enhance technical training and support; strengthen links between producers and buyers; and expand the market for Shan Tuyet tea in Yen Binh.